Microwave pyrolysis with KOH/NaOH mixture activation: A new approach to produce micro-mesoporous activated carbon for textile dye adsorption - Liew, Rock Keey; Lam, Su Shiung; Cheng, C. K.; Elfina, Azwar; Yek, Peter Nai Yuh; Lim, Xin Yi; Ng, Jo Han; Ahmad, Jusoh; Lam, Wei Haur; Mohd Danial, Ibrahim; Ma, Nyuk Ling (Elsevier, 2018)
A micro-mesoporous activated carbon (AC) was produced via an innovative approach combining microwave pyrolysis and chemical activation using NaOH/KOH mixture. The pyrolysis was examined over different chemical impregnation ratio, microwave power, microwave irradiation time and types of activating agents for the yield, chemical composition, and porous characteristic of the AC obtained. The AC was then tested for its feasibility as textile dye adsorbent. About 29 wt% yield of AC was obtained from the banana peel with low ash and moisture (< 5 wt%), and showed a micro-mesoporous structure with high BET surface area (≤ 1038 m 2/g) and pore volume (≤ 0.80 cm 3/g), indicating that it can be utilized as adsorbent to remove dye. Up to 90% adsorption of malachite green dye was achieved by the AC.